Wacana Puja Bhakti Dalam Kakawin Raja Patni Mokta - I Nyoman Suwana; I Nyoman Suarka; Ida Bagus Rai Putra (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2016)
This study analyzes the tribute discourse in Kakawin Raja Patni Mokta. The composition of this kakawin is dominated by the theme of tribute for first lady, Tien Soeharto. The focus of this research are to reveal the form of puja bhakti (tribute), its function, and its meaning in Kakawin Raja Patni Mokta. Semiotic theory from Pierce is used to intreprete the text, while sociological theory of literature by Wellek and Werren is used to analyze the function of tribute discourse in Kakawin Raja Patni Mokta. Puja Bhakti in Kakawin Raja Patni Mokta can be considered as a special offering to the nation